Intracranial Arteriopathy and Ischemic Stroke - J Gordon Millichap (Pediatric Neurology Briefs, 2009)
Repeated vascular imaging findings and clinical charts of 79 children with anterior circulation arterial ischemic stroke (AIS) and unilateral intracranial arteriopathy of the internal carotid bifurcation were studied at the University Medical Center, Utrecht, The Netherlands, and other centers in France, UK, and Canada.